GRS 1739-278 observed at very low luminosity with XMM-NEWTON and NuSTAR - Fürst, F.; Tomsick, J.; Yamaoka, K.; Dauser, T.; Miller, J.; Clavel, M.; Corbel, S.; Fabian, A.; García, J.; Harrison, F.; Loh, A.; Kaaret, P.; et al. (Institute of Physics Publishing, 2016)
We present a detailed spectral analysis of XMM-Newton and NuSTAR observations of the accreting transient black hole GRS 1739−278 during a very faint low hard state at ∼0.02% of the Eddington luminosity (for a distance of 8.5 kpc and a mass of 10 M ). The broad-band X-ray spectrum between 0.5–60 keV can be welldescribed by a power law continuum with an exponential cutoff. The continuum is unusually hard for such a low luminosity, with a photon index of Γ = 1.39 ± 0.04. We find evidence for an additional reflection component from an optically thick accretion disk at the 98% likelihood level. The reflection fraction is low with Rrefl = 0.043+0.033 −0.023. In combination with measurements of the spin and inclination parameters made with NuSTAR during a brighter hard state by Miller and co-workers, we seek to constrain the accretion disk geometry. Depending on the assumed emissivity profile of the accretion disk, we find a truncation radius of 15–35 Rg (5–12 RISCO) at the 90% confiden